Drivers of exchange rate dynamics in selected CIS countries: Evidence from a FAVAR analysis - Christian Dreger; Jarko Fidrmuc (Osteuropa-Institut Regensburg, 2010)
We investigate the likely sources of exchange rate dynamics in selected CIS countries (Russia, Kazakhstan, Ukraine, Kyrgyzstan, Azerbaijan, and Moldova) over the last dec-ade (1999-2010). Evidence is based on country VARs augmented by a regional com-mon factor structure (FAVAR model). The models include nominal exchange rates, the common factor of exchange rates in the CIS countries, and international drivers such as global trade, share prices, and oil price. Global, regional and idiosyncratic shocks are identified in a standard Cholesky fashion. Their relevance for exchange rates is ex-plored by a decomposition of the variance of forecast errors. The impact of global shocks to in the developments of exchange rates has increased, in particular, if financial shocks are considered. Because of the financial crisis, regional shocks have become more important at the expense of global shocks.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F31; C22; G15; 330; Exchange rates; CIS countries; financial crisis; FAVAR models; Wechselkurs; Volatilität; Schock; Finanzmarktkrise; GUS-Staaten